PENERAPAN METODE PROFILE MATCHING DALAM MEREKOMENDASIKAN BIBIT KELAPA SAWIT - Ika Septi Mahdia; Solikhun Solikhun; M. Fauzan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Oil palm plants are plantation crops that are cultivated and require intensive care, oil palm seeds are a major factor in the success of oil palm plantation cultivation. Quality palm oil seedlings will provide satisfactory yields, oil palm seedlings should be obtained with superior seed selection and good maintenance, in nurseries carried out by following the existing stages, oil palm plantations are long-term business and maintenance of oil palm seeds must be be considered and managed with incentives to ensure optimal production and business results in the future. This study aims to determine quality oil palm seeds in PTPN IV Bah Jambi Plantation. In the nursery is carried out by following the existing stage, this research uses Decision Support System (SPK) Profile Matching method. This method can be used to solve semi-structured problems by calculating consistency using the Profile Matching method, if consistent values are generated consistently can be used as a reference for ranking quality oil palm seeds in PTPN IV Bahjambi Plantation. For the results of the research it can be produced that it is easier to recommend oil palm seedlings and be an input to the plantation in recommending the best oil palm seeds.Keywords: Palm oil seeds, Decision Support System, Profile Matching